Social and cultural aspects of language learning in study abroad - Kinginger, Celeste, 1959- (Language learning and language teaching, 2013)
This chapter seeks to demonstrate some of the potential contributions of a corpus-based approach to study abroad research. Drawing on the Spanish Learner Language Oral Corpora, the present analysis examines a set of vague expressions known as general extenders (GEs) (Overstreet 1999) utilized by undergraduate English L1 learners after a year abroad. Specifically, the analysis focuses on patterns emergent from the concordancing analysis of learner language production alongside four exploratory case studies of learners' motives and dispositions towards their study abroad experience. The discussi.